Evaluation of market efficiency for supplementary accounting disclosures: The case of pension assets and liabilities* - LANDSMAN, WAYNE R.; OHLSON, JAMES A. (Contemporary Accounting Research, 1990)
This paper examines the extent to which stock prices fully reflected the off‐balance‐sheet item net over‐ (under‐) funded pension liabilities during the four‐year period 1979–82. The evidence suggests that the market was informationally inefficient and that it displayed a general underreaction relative to the net pension liability. Significant excess returns could have been earned by using the net pension liability as an instrument for portfolio selection. The empirical analysis fails to identify the existence of confounding variables such as beta risk, size, or industry effects. Résumé. Les auteurs examinent dans quelle mesure le cours des actions a reflété l'évolution du poste net hors bilan de l'excédent (ou du déficit) de provisionnement de la dette au titre des régimes de retraite, pendant la période de quatre ans écoulée entre 1979 et 1982. Les constatations des auteurs laissent supposer que le marché était inefficient sur le plan informationnel et qu'il a enregistré une réaction générale mitigée à la dette nette au titre des régimes de retraite. L'utilisation de la dette nette au titre des régimes de retraite comme critère de sélection de portefeuilles aurait permis d'obtenir des rendements excédentaires importants. L'analyse empirique ne parvient pas à déterminer l'existence de variables contradictoires telles que le risque Beta, la taille ou les effets du secteur.